From the Periphery to a Global Player : Historical Evolution of the Qatari Banking Sector - Abumughli, Ala’ Azmi; Aysan, Ahmet Faruk; Arslan, Ahmad; Gölgeci, İsmail; Bouguerra, Abderaouf (Palgrave Macmillan, 2024)
The incredibly rapid and remarkable rise of the banking industry in Qatar contains valuable historical lessons that the extant research has so far overlooked. We rely on the elite interviews with the pivotal players of the banking industry over the last several decades and archival data to present a history of the banking sector in Qatar. Our paper explains the key milestones in Qatar’s banking sector and reveals the changes in Qatar’s economic structure vis-a-vis the evolution of the banking sector. The findings also reveal the vital role of British banks in the early phases of this evolution and how local family businesses played an instrumental role in developing local banks, along with targeted state policies. Thus, our paper distinctly sheds light on the lesser-known period of the 1950s to 1980s of the Qatari economy by analyzing the evolution of its banking sector.
Keywords: Arabian Gulf; Banking; Evolution; Financial Services; history; Qatar